Phase variations of the summer and winter seasons in the Bohai Sea during the last four decades - Yuan, Chengyi; Kuang, Xiaodi; Xu, Jingbo; Li, Ruopeng; Wang, Chen (Frontiers in Marine Science, 2023)
To mirror the reality of the ongoing climate change, the summer and winter seasons in the Bohai Sea are redefined using the local water temperature thresholds. During the last four decades, the phase variations of the seasons were quantified using the season duration and transition timing indices, including the duration (DUR), onset (ONS), and withdrawal (WIT) calculated on the basis of the OSTIA SST dataset at a very high resolution (0.05 °). During 1982–2019, the summer DUR has an accumulated increase of about 17 days (4.5 days decade-1), which is primarily induced by the phase advance of the summer ONS by about 16 days (4.2 days decade-1), rather than the slight delay of the summer WIT. Spatial features of the duration and timing indices demonstrate that the lengthening of summer DUR and the phase advance of summer ONS have significantly enhanced in the shallow regions, due to the limited thermal inertia and shorter period of the ocean’s memory. In contrast, the secular trend of winter DUR exhibits an accumulated shortening of about 18 days (4.8 days decade-1), which is induced by a moderately delayed winter ONS of 6 days (1.6 days decade-1) and a significantly advanced winter WIT of 12 days (3.2 days decade-1). The potential linkage between the phase variations in the oceanic seasonal cycle and those of the atmospheric forcing was investigated by analyzing both the interannual variability and the secular trend. Our results highlight the influence of cloud cover in addition to wind speed on the timing of season transitions. Over the analysis period, the secular trend of an earlier summer ONS is related to a total reduction of cloud cover by 30% of its climatological mean and an increase of incoming solar radiation of 10 W m-2 month-1 in the late spring. Understanding the phase variations of seasons in the Bohai Sea is crucial to revealing the response of coastal oceans to global warming.